An evaluation of training and development policies and processes of a textile enterprise: A case study on Beximco Limited (Textiles and Apparel Division) - Ahmed, Kazi Moudud (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.